A xilogravura expressionista brasileira - Varela, Marcos Baptista (1997)
This dissertation intends to verify the permanency of the expressionist language in the brasilian woodcut, the way it happens as a constant trend in brazilian modem print. It will be studied the varied definitions of Expressionism as language in Modem Art; the woodcut as artistic expression in History; it's evolution until german expressionist woodcut in first years of XXth century. Afterwards it will be approached the woodcut in Brazil, since it's begining, it's development as autonomous artistic manifestation after Modem Art Week in 1922, through the first woodcuters: Lasar Segall, Oswaldo Goeldi and Lívio Abramo. Later it will be studied the posteriors generations of expressionist woodcutters influenced by pioneers, which works manifested socio-political purposes or autonomous, with personal language until 70's. It will be observed the persistency of a expressionist language in woodcut with large personal manifestations, until today.